1980
DOI: 10.1246/bcsj.53.1414
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Methyl (Methylthio)methyl Sulfoxide

Abstract: Oxidation of methyl (methylthio)methyl sulfoxide (2) with hydrogen peroxide in acetic acid or methanol produced bis(methylsulfinyl)methane in high yield. Similar results were obtained in oxidation of 2 with ozone, sodium metaperiodate, and m-chloroperbenzoic acid. In contrast, methyl (methylthio)methyl sulfone (4) was exclusively formed when oxidation of 2 with hydrogen peroxide was carried out in methanol in the presence of sodium hydroxide. Furthermore, we established a convenient and efficient method of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 5 publications
3
17
0
1
Order By: Relevance
“…This result is consistent with the work of Ogura et al (19) who found that methyl (methy1thio)methyl Results sulfoxide, 1, was oxidized by permanganate to methyl (methThe products were analyzed by HPLC. Chromatograms were y1thio)methyl sulfone, 2, in 97% yield.…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the work of Ogura et al (19) who found that methyl (methy1thio)methyl Results sulfoxide, 1, was oxidized by permanganate to methyl (methThe products were analyzed by HPLC. Chromatograms were y1thio)methyl sulfone, 2, in 97% yield.…”
Section: Discussionsupporting
confidence: 92%
“…The reaction outcome of the oxidation of the equatorial sulfoxide 13 was strongly dependent on the oxidant used. It has already been noted by Ogura et al25,28 for related compounds that nucleophilic oxidants like permanganate attack the sulfur of the more electrophilic sulfoxide and not the sulfide in the molecule. Accordingly, when we exposed sulfoxide 13 to potassium permanganate we obtained the sulfone 14 in an excellent 86 % yield (entry 6).…”
Section: Resultsmentioning
confidence: 91%
“…The best results for the preparation of sulfoxide 13 were achieved with sodium periodate25 or a hydrogen peroxide/urea complex (UHP) in the presence of acetic acid,26 which gave sulfoxide 13 in yields of 74 and 70 %, respectively (Table 1, entries 1 and 2). A minor product was the axial sulfoxide 12 (<10 %), which could not be separated after purification of the crude material.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ftue: ácido periódico, obteve-se, após mna hora de reação, mna mistura não identificada de produtos. Em mna outra tentativa, empregando-se mna mistura de ácido acético glacial e solução de peróxido de hidrogêni0 161 30 % e, variando as quantidades e a ordem de adição de reagentes, obtiveram-se, em todos os casos, misturas de sulfonil e sulfmil ácidos correspondentes, ao lado do reagente de partida e, em alguns casos, produtos provenientes da descarboxilação destes compostos. Tentou-se também C:…”
Section: Métodos De Oxidaçãounclassified